CT-guided radiofrequency ablation of osteoid osteoma: established concepts and new ideas - Singh, Dharmendra Kumar (Br J Radiol, 2020)
Osteoid osteoma is a painful benign bone tumour of children and young adults with characteristic clinico-radiological features depending upon the location of the lesion. Intraoperative visualisation of the nidus is difficult and therefore curative surgery is often associated with excessive bone removal, significant perioperative morbidity and potential need of bone grafting procedures. With advancement in cross-sectional imaging and radiofrequency ablation (RFA) technology, CT-guided RFA has emerged as the treatment of choice for the osteoid osteoma. This procedure involves accurate cannulation of the nidus and subsequent thermocoagulation-induced necrosis. Multidisciplinary management approach is the standard of care for patients with osteoid osteoma. Appropriate patient selection, identification of imaging pitfalls, pre-anaesthetic evaluation and a protocol-based interventional approach are the cornerstone for a favourable outcome. Comprehensive patient preparation with proper patient position and insulation is important to prevent complications. Use of spinal needle-guided placement of introducer needle, namely, “rail–road technique” is associated with fewer needle trajectory modifications, reduced radiation dose and patient morbidity and less intervention time. Certain other procedural modifications are employed in special situations, for example, intra-articular osteoid osteoma and osteoid osteoma of the subcutaneous bone in order to reduce complications. Treatment follow-up generally includes radiographic assessment and evaluation of pain score. Dynamic contrast-enhanced MRI has been recently found useful for demonstrating post-RFA healing.